Mechanical sensorless LPV torque ripple control of hybrid electric vehicle. Issue 16 (5th September 2017) - Cauet, Sebastien; Etien, Erik; Rambault, Laurent
Abstract : This research concerns the vibration reduction transmitted by the thermal engine to the drivetrain. In the context of a hybrid electric vehicle, the use of an electric synchronous machine, more specifically a permanent magnet synchronous machine, is recommended to partly ensure vehicle propulsion but also to mitigate the torque pulsations generated by the engine. Most strategies using this propulsion method require a very accurate position sensor. However, instead of using a sensor, this research proposes the use of a position/speed observer. This approach is combined with linear parameter varying control to guarantee consistent performance during speed transients. Thus, this strategy does not use additional hardware for a hybrid drive and consumes very little additional electrical energy (excluding the electrical losses in the motor and the inverter). These methods are illustrated within the context of an urban trip and clearly show the effectiveness of the proposed approach.